THE ROLE OF NITRIC OXIDE IN DEVELOPMENT OF SKIN DISEASES - I.Yu. Smirnova; L.M. Ogorodova; I.A. Deev ("Paediatrician" Publishers LLC, 2009)
Endogenous nitric oxide (NO) influences on the processes taking place in skin by different ways as in norm, as in pathology. Constitutive (neuronal and endothelial) and inducible NO-syntases, responsible for NO synthesis, produce unequal volumes of it. This fact, finally, determine the degree of their participation in processes of skin reparation, and development of such diseases as psoriasis, melanoma, atopic dermatitis. Key words: skin, nitric oxide, NO-syntases. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(4):90-94)